Compounding Disadvantage: The Effects of School and District Size on Student Achievement in West Virginia - Craig Howley (Journal of Research in Rural Education, 1996)
This investigation replicated a California study that reported substantial school- and district-size effects on achievement-effects that interacted with the socioeconomic status ofthe community (Friedkin & Necochea, 1988). Using a 1990 West Virginia data set, Ifound evidence ofsimilar relationships, and in circumstances that differed sharply from those in the original study. Small schools facilitated the academic achievement ofimpoverished students, whereas large schools facilitated the academic achievement ofaffluent students. The difference in West Virginia was that impoverished students most often attended small schools. Implications are drawn for the development offuture policy and for future research into effects ofschool and district size.